Case series of gastrointestinal stromal tumors with lymph nodes metastasis: unusual presentations - Fahimy, M. Afiq M.; Fan, Ling L.; Ramasamy, Umasangar (International Surgery Journal, 2021)
Gastrointestinal stromal tumor (GIST) is a rare cancer of the gastrointestinal tract, it occurred about 0.1-3.0% of all gastrointestinal neoplasms. Accounted about 10% of small-bowel tumors, and 10-15% of all sarcomas. Liver is a common hematogenous spread in GIST. However, metastasis to lymph nodes is consider extremely rare and routine lymph node dissection for GIST tumor was not recommended. Hence, we reported a case series of GIST that metastasize to lymph node along our experience in our center, hospital Taiping, Malaysia from 2010 until 2020. Hereby we report total of 3 out of 18 GIST cases that we encountered confirmed through histopathology the existence of lymph node metastasis.